SOUTH CAUCASUS IN THE US FOREIGN POLICY SYSTEM IN 1991-2001 - Ludmila Velichko (Гуманитарные и юридические исследования)
The change in priorities in the foreign policy course of Washington coincides with the presidential term of this or that president. Modern researchers talk about «presidential doctrines» that were a response to changing historical realities. The Cold War, which ended in the collapse of the Soviet system, influenced the design of the idea of global leadership of the United States, which was formulated in the Clinton Doctrine. The author made an attempt to reveal the peculiarities of the geopolitical strategy of the United States to establish control over Heartland during the formation of a new foreign policy system. The article shows the South Caucasus not so much as an arena of rivalry between Washington and Moscow, but as the region, where one tested the technologies of foreign policy cooperation with the new States that emerged in the post-Soviet space, primarily Russia, which considers the Caucasus to be the zone of its unconditional influence. In an effort to ill the strategic vacuum, the United States has used various levers of influence on Georgia, Armenia, and Azerbaijan to weaken Russia's influence and prevent Iran and Turkey from becoming more active. It was the policy of «trial and error», which showed that the United States would not have absolute leadership here, but it was during that period when Washington managed to solve the main problem - to prevent full control of Russia over the «Eu-rope - Asia bridge».